Peran Media Pembelajaran TIK untuk Mendukung Pembelajaran PAI yang Interaktif di Madrasah Muallimat Muhammadiyah Yogyakarta - Windi Astuti, Anggun (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze and describe the application of ICT-based learning media in PAI subjects at Madrasah Muallimat Muhammadiyah Yogyakarta. This research uses a qualitative method. Data was collected through theoretical analysis, documentation and direct interviews with subject teachers. The results of this study explain that the application of ICT-based learning media, such as the use of learning applications and videos, can increase students' attention and involvement in the classroom. This refers to improving the quality of learning, especially in attracting students' attention and focus on the material being taught. Variety in media use is also necessary to prevent students from becoming bored. Overall, ICT-based media helps students better understand PAI material and is considered a necessity in today's learning.